Congenital adrenal hyperplasia in Malaysian paediatric endocrine tertiary centre: A review of cases and growth outcome / Nurmaira Hashim - Nurmaira, Hashim (2017)
Introduction: Congenital adrenal hyperplasia(CAH) is a group of autosomal recessive disorder resulting in abnormality of cortisol aldosterone and/or testosterone synthesis. The worldwide incidence is between 1: 10000-20000. There are limited data on CAH children in Malaysia. We aim to describe the clinical phenotypes of CAH and growth outcome among children with CAH as well as other associated related complications. Methods: We reviewed 38 eligible patients' notes seen between 1982-2016. CAH was classified as classical [salt wasting(SW) or simple virilizing(SV)] or nonclasical(NCCAH). Enzyme diagnosis was made following clinical presentation of AG and SW with supportive biochemical parameters. This is confirmed with raised l7OHP and testosterone level. Auxology biochemical parameters and dose of glucocorticoids were reviewed at 5 different time points; 2 year, 5 year, 10 years, 15 year and at final height.